Analisis Proses Tapping Pada Pembuatan Produk Joint Brake Rod KTMY Untuk Sepeda Motor Honda - Harliansyah, Reynaldi; Santoso, Deri Teguh (Universitas Nusantara PGRI Kediri, 2022)
The tapping process on the ktmy joint brake rod and uncertainty during the deep tapping process with different sizes are serious problems so this research has the aim of being able to find out more about the tapping process to make threads and be able to find out the types of tapping eye sizes. which is used to make threads. Field studies carried out in this practical work activity were by visiting directly to the production department of PT. Ciptaunggul Karya Abadi. The data used in this study were obtained from data regarding uncertainty during the tapping process if it is intended to make internal threads of different sizes that occur in the Taiwan Tapping Machines M32 semi-automatic tapping machine and also the interview method conducted directly. The data that has been obtained is then continued by designing a fishbone diagram. From the results of the study, based on the results of the analysis using the fishbone diagram method about broken pins on the tapping machine, there are 4 influencing factors, namely: material, method, machine, and human. Of these 4 factors, the biggest influence on the broken pin on the Taiwan Tapping Machines M32 type tapping machine is the manpower and method. This is because the operator has only worked for less than a month, there is no retraining and the SOP (Standard Operational Procedure) is not posted on the machine work area.